Mechanical properties of oriented strand board from kelempayan wood at different resin content / Wan Mohd Nazri Wan Abdul Rahman, Jamaludin Kasim and Rahim Sudin - Wan Abdul Rahman, Wan Mohd Nazri; Kasim, Jamaludin; Sudin, Rahim (2003)
Wood innovation in manufacturer spans a very wide range of science and technology. Oriented strand board (OSB) is a new type of wood composite, which is yet to be commercially produced in Malaysia or South East Asia region. OSB is made from long thin and narrow wood strands bonded with resin and converted into panel during the hot pressing operation. This study was carried out with the objective of obtaining the mechanical properties (MOE, MaR and IB) of OSB from Kelempayan wood with 650 kgm 3 at three different resin content (3%, 5% and 7%). Among the three levels of resin content, specimens with 7% has the highest value of MOE, MOR and lB. It was observed that the higher resin content in the board specimen gives better mechanical properties. All test results of the specimen (MOE, MOR and IB) passed the standard. As a conclusion to this study, Kelempayan wood is a potential and suitable species as a raw material for the production of OSB.